Understanding the extremely impoverished: an exploration into the lives of the poor in Upper Egypt - Frazier, Shanaya (AUC Knowledge Fountain, 2013)
Within an area of Luxor named Al Qurna (within Upper Egypt) there exist a great number of individuals and families living in extreme poverty. For many who are impoverished in this area, charitable donations are the only source of income and way of meeting necessities. While these donations are appreciated, it is far from enough and do not supply an efficient amount of income to dismiss impoverished circumstances. By ethnographically exploring the lives of the poor in Al Qurna using semi-informal interviews and participant observation, I was able to experience firsthand the creative ways they survive with the small amount of necessities provided to them. I was also able to get to know what social factors contribute to creating and maintaining poverty in the region. The individuals that I studied are extremely poor, yet they are able to survive and get by on what little they have available to them. This research offers an in depth look into the fears, social circumstances, creativity, activities, resources, and life experiences of the poor. The realities that were revealed may be considered unimaginable, yet they enable an understanding of poverty as experienced and perceived by the poor themselves